Korelasi antara Kadar Kalsidiol (25-Oh) dan Rasio Netrofil-Limfosit dengan Keganasan Nodul Tiroid - Bogar, Bryan D.; Lumintang, Nico; Tandililing, Sherly; Wariki, Windy M. (e-CliniC, 2024)
Abstract: Thyroid malignancy has shown the highest annual incidence rate. Vitamin D deficiency (serum 25-hydroxyvitamin D levels) is one of the risk factors for thyroid malignancy. The neutrophil-lymphocyte ratio (NLR) reflects the balance between pro-tumor inflammatory response and anti-tumor immune response. This study aimed to investigate the relationship between serum 25-hydroxyvitamin D levels, NLR, and thyroid nodule malignancy. This was an observational and analytical study with cross-sectional design. Samples were patients with thyroid nodules admitted to Prof. Dr. R. D. Kandou Hospital, Manado, form August 2022 to March 2023. The results obtained a total of 46 patients with thyroid malignancy that  met the inclusion criteria. The patient characteristics were predominantly female (82.6%), with a mean age of 50.2 ± 14.74 years, normal thyroid hormone status (82.6%), mean serum 25-hydroxyvitamin D levels of 32.25 ng/mL, mean NLR of 5, and papillary carcinoma as the most common malignancy (43.48%). Spearman's correlation analysis revealed a significant association between thyroid malignancy and serum 25-hydroxyvitamin D levels (r =-0.501, p=0) as well as NLR (r 0.376, p=0.01). In conclusion, serum 25-hydroxyvitamin D levels and NLR can be used as indicators for predicting thyroid nodule malignancy. Keywords: thyroid malignancy; 25-hydroxyvitamin D; neutrophil-lymphocyte ratio   Abstrak: Keganasan tiroid mengalami peningkatan angka kejadian tertinggi pertahun. Kekurangan vitamin D (kadar kalsidiol) merupakan salah satu faktor risiko terjadinya keganasan tiroid. Rasio netrofil limfosit (RNL) mencerminkan keseimbangan antara respon inflamasi protumor dan respon imun antitumor. Penelitian ini bertujuan untuk mengevaluasi hubungan antara kadar 25-hydroxyvitamin D serum dan RNL dengan keganasan nodul tiroid. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Sampel penelitian ialah pasein dengan nodul tiroid yang dirawat di RSUP Prof. Dr. R. D. Kandou Hospital, Manado, sejak Agustus 2022 s/d Maret 2023. Hasil penelitian mendapatkan 46 pasien dengan keganasan tiroid yang memenuhi kriteria. Karakteristik sampel tebanyak ialah jenis kelamin perempuan (82,6%), rerata usia (50,2±14,74 tahun), status hormon tiroid normal (82,6%), rerata kadar 25-hydroxyvitamin D 32,25 ng/mL, rerata RNL 5, dan jenis keganasan karsinoma papiler (43,48%). Uji analisis Spearman menunjukkan keganasan tiroid secara bermakna berhubungan dengan kadar kalsidiol (r=-0,501, p=0), dan RNL (r=0,376, p=0,01). Simpulan penelitian ini ialah kadar 25-hydroxyvitamin D serum dan RNL dapat digunakan sebagai indikator untuk memrediksi keganasan nodul tiroid. Kata Kunci: keganasan tiroid; 25-hydroxyvitamin D; rasio netrofil-limfosit